Introductory business statistics - Tiemann, Thomas K.; BC Open Textbook Project; BCcampus (Global Text, 2010)
"Introductory Business Statistics provides students with an intuitive understanding of sampling distributions and their place in hypothesis testing. This texts aims to help students understand how statistics works, not just how to "get the right number"."--BCcampus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on version viewed on BCcampus OpenEd website; title from pdf title page.
Keywords: Commercial statistics -- Textbooks; Electronic books